2017
DOI: 10.1136/bcr-2017-220814
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of chronic cyanide toxicity from self-prescribed apricot kernel extract

Abstract: Hypoxia under general anaesthesia is a potentially life-threatening condition. A seemingly well 67-year-old man appeared hypoxic with peripheral pulse oximetric measurement during routine anaesthesia. Postoperatively, the patient admitted to daily self-prescription of apricot kernel extract for a period of 5 years. Apricot kernel is a commonly taken extract used for a range of ailments, and is associated with cyanide toxicity, which was confirmed through blood analysis. Our explanation for the hypoxic measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Patients were also discouraged from using herbal remedies with potential safety issues, such as apricot seeds with reported cyanide toxicity. 29 A previous study has suggested that a majority of patients (60%) with haematological cancer in Malaysia did not voluntarily inform their physicians about their CAMs usage. 30 Therefore, pharmacists play an essential role in reviewing the use of CAMs by CML patients and monitoring these patients for potential drug-vitamin-herb interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were also discouraged from using herbal remedies with potential safety issues, such as apricot seeds with reported cyanide toxicity. 29 A previous study has suggested that a majority of patients (60%) with haematological cancer in Malaysia did not voluntarily inform their physicians about their CAMs usage. 30 Therefore, pharmacists play an essential role in reviewing the use of CAMs by CML patients and monitoring these patients for potential drug-vitamin-herb interactions.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Apricot seeds toxicity stems from the chemical compound amygdalin, 35,37,38 which is naturally occurring in many plants, but most notably in the seeds of apricots, bitter almonds, plums, apples, and peaches. 35,37,38 Amygdalin is often sold under the name "Vitamin B17," despite not being a vitamin, and a semisynthetic form known as laetrile 36,37 was used as an alternative cancer therapy before being banned by the FDA in 1978. 36 Amygdalin is toxic because when ingested, it is readily metabolized by the enzyme beta-glucosidase to hydrocyanic acid, or cyanide.…”
Section: Semen Armeniacae Amarum (Xing Ren)mentioning
confidence: 99%
“…35,37,38 Later signs include nausea, vomiting, arrythmias, coma, pulmonary edema, and renal failure. 35,37,38 The diagnosis is often made clinically, but a profound lactic acidosis is often seen on laboratory values and may aid in making the diagnosis. 37,38 Serum cyanide levels can be drawn but typically will not result in sufficient time to aid in treatment of the patient.…”
Section: Semen Armeniacae Amarum (Xing Ren)mentioning
confidence: 99%
“…It was then discovered that the patient self‐administered three 2 g tablets of Novodalin (a proprietary amygdalin preparation) and had two teaspoons of home‐made apricot kernel extract per day. Analysis of Novodalin showed cyanide levels of 220 mg/kg and the homemade apricot kernel extract 1,600 mg/kg of cyanide, meaning that the patient ingested daily approximately 17.32 mg of oral cyanide (Konstantatos et al., ). While the high blood cyanide level is explained by the ‘medication’ of the patient, it should be noted that cyanide intoxication does not lead to blood hypoxia.…”
Section: Assessmentmentioning
confidence: 99%